2014
DOI: 10.1016/j.redox.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification of cytoskeletal proteins in neuronal cells by tryptamine-4,5-dione

Abstract: Serotonin, 5-hydroxytryptamine, is a systemic bioactive amine that acts in the gut and brain. As a substrate of myeloperoxidase in vitro, serotonin is oxidized to tryptamine-4,5-dione (TD), which is highly reactive with thiols. In this work, we successively prepared a monoclonal antibody to quinone-modified proteins and found that the antibody preferentially recognizes the TD–thiol adduct. Using the antibody, we observed that the chloride ion, the predominant physiological substrate for myeloperoxidase in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
(30 reference statements)
0
24
0
Order By: Relevance
“…( 36 ) Chloride ions at physiological concentrations do not compete with TD-derived modifications, suggesting that serotonin is a promising physiological substrate of myeloperoxidase in vivo . ( 37 ) Cytoskeletal proteins, α- and β-tubulins, vimentin, and neurofilament-L, in SH-SY5Y neuroblastoma cells have been identified as target proteins. Self-polymerization of tubulins was modulated by the exposure of TD in vitro .…”
Section: Products Derived From Peroxidase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…( 36 ) Chloride ions at physiological concentrations do not compete with TD-derived modifications, suggesting that serotonin is a promising physiological substrate of myeloperoxidase in vivo . ( 37 ) Cytoskeletal proteins, α- and β-tubulins, vimentin, and neurofilament-L, in SH-SY5Y neuroblastoma cells have been identified as target proteins. Self-polymerization of tubulins was modulated by the exposure of TD in vitro .…”
Section: Products Derived From Peroxidase Activitymentioning
confidence: 99%
“…It has also been confirmed that the metabolite of serotonin, 5-hydroxyindoleacetic acid, is a favorable substrate and that the successive formation of quinone gives rise to the covalent conjugation of protein thiols. ( 37 ) It has been shown that urate is also a possible physiological substrate for myeloperoxidase. ( 38 ) These results suggest that myeloperoxidase may use many endogenous substrates in vivo .…”
Section: Products Derived From Peroxidase Activitymentioning
confidence: 99%
“…Oxidative modification of intracellular and membrane components of vascular endothelial cells may lead to the development of endothelial dysfunction, vascular damage and atherosclerosis. A causal relationship was documented by the accumulation of MPO in atherosclerotic lesions [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…( 40 ) As shown below, the quinone-modified protein was immunochemically detected on a membrane or fixed tissue, indicating that adducted quinone on a protein is relatively stable. ( 41 , 42 )…”
Section: Generation Of Quinones and Reaction Toward Biomoleculesmentioning
confidence: 99%
“…( 9 , 19 , 40 ) Specific antibodies to quinone or quinone adduct have also been used for immunochemical detection. ( 42 , 49 , 50 )…”
Section: Generation Of Quinones and Reaction Toward Biomoleculesmentioning
confidence: 99%